ANALISIS PENGARUH FAKTOR RISIKO KECURANGAN (DIAMOND FRAUD) TERHADAP MANAJEMEN LABA DENGAN STATUS SANKSI SEBAGAI VARIABEL MODERASI - Dewi, Cahya Kusuma (Jurnal Ilmiah Mahasiswa FEB, 2017)
The study aimed to determine effect of fraud risk factors in fraud diamond as the independent variable which was proxied through Return On Asset (ROA), proportion of independent board, change in auditor and change of directors on earnings management with status of sanctions as the moderating variable. The sample were the companies listed on the Stock Exchange in period 2013-2015 are classified into companies that commit fraud and the company did not commit fraud. Companies that commit fraud are determined based on the sanctions by Otoritas Jasa Keuangan related to the violation of the regulations of VIII.G.7 regarding the presentation anddisclosure of financial statements of listed public companies. Based on a purposivesampling technique used, there were 12 companies that commit violation and 22companies that did not commit violation. Hypothesis testing was conducted usingmoderated regression analysis with SPSS 22 software. The result gives the evidencethat only proxy ROA has a significant effect on earnings management. Status sanctionas moderating variable has no significant effect on earnings management. Keywords: diamond fraud, return on asset (ROA), proportion of independent board, change in auditor, change of directors, status of sanction,earnings management.